Synthesis of High‐Molecular‐Weight and Strength Polyisobutylene‐Based Polyurethane and Its Use for the Development of a Synthetic Heart Valve. Issue 1 (25th October 2022) - Deodhar, Tejal; Nugay, Nihan; Nugay, Turgut; Patel, Ruhi; Moggridge, Geoff; Kennedy, Joseph Paul
Abstract: Under optimized synthesis conditions, for the first time, polyisobutylene‐based polyurethane (PIB–PU) is prepared with 70% PIB soft segment (i.e., a bioinert and calcification‐resistant PU) with M n > 100 000 Da, 32 MPa ultimate strength, and 630% elongation. The key parameters for this achievement are a) the precise stoichiometry of the polyurethane forming reaction, specifically the use of highly purified di‐isocyanate (4, 4′‐methylene‐bis (phenyl isocyanate), MDI), and b) the increased solid content of the synthesis solution to the limit beyond which increased viscosity prevents stirring. The shape of the stress–strain trace of PIB–PU indicates a two‐step failure starting with a reversible elastic (Hookean) region up to ≈50% yield, followed by a slower linearly increasing high‐modulus‐deformation region suggesting the strengthening of PIB soft segments by entanglement/catenation, and the hard segments by progressively ordering urethane domains. This PIB–PU is a candidate for a fully synthetic bioprosthetic heart valve since preliminary studies show that PIB–PU has impressive fatigue life. Abstract : The improved synthesis of polyisobutylene‐based polyurethane (PIB–PU) containing 70 wt% PIB leads to superior thermoplastic elastomers for the preparation of a fully synthetic bioprosthetic heart valve and other impantable medical devices.